Effectiveness of a Self-Instructive Educational Approach on Knowledge and Attitude Regarding Immunization of Under-Five Children Among Nursing Students - Meghwal, Kastoor Chand; Kumar, Periadurachi (Journal of Neonatal Surgery, 2025)
Background: Immunization is a vital public health intervention, and nursing students play a key role in vaccine promotion and delivery. However, gaps in knowledge and passive attitudes among students may hinder effective vaccine advocacy. Aim: To evaluate the effectiveness of a self-instructional educational module in improving nursing students’ knowledge and attitude toward immunization of under-five children. Methods: A pre-experimental one-group pre-test post-test design was used among 87 third- and fourth-year nursing students. A validated self-instructional module was administered, and knowledge and attitude were assessed using structured questionnaires before and after the intervention. Results: Post-intervention, students with “good” knowledge scores increased from 9.2% to 64.4%, and those with favorable attitudes rose from 14.9% to 65.5%. A significant positive correlation (r = 0.62, p < 0.001) was found between knowledge and attitude. Associations were observed between pre-test knowledge and prior immunization program participation (p = 0.048), and between favorable attitudes and source of immunization knowledge (p = 0.039). Conclusion: The self-instructive module significantly enhanced students’ knowledge and attitudes toward childhood immunization. Integrating such tools into nursing education can prepare students as effective immunization advocates